Experimental researches on sliding mode active vibration control of flexible piezoelectric cantilever plate integrated gyroscope - Qiu, Zhi-cheng; Wu, Hong-xin; Zhang, Dong (Thin-walled structures, 2009)
The flexible appendages of spacecrafts in aerospace applications demand to be lighter and larger. Thus, they are susceptible to excessive vibration response due to external disturbances or attitude maneuvering. Some of the flexible appendages are cantilever plate structures, such as solar panels and plate shape antennas. Usually, the coupled bending and torsional vibration of cantilever plate will be caused. To decouple the bending and torsional vibration for measuring and driving, gyroscope and PZT patches are used as sensors and actuators by utilizing optimal placement. The motion of equation of the presented piezoelectric plate system is derived. And a kind of discrete-time sliding mode variable structure control (VSC) algorithm is proposed to suppress vibration of the flexible plate. The experimental comparison studies are conducted. The experiments demonstrate that the proposed methods can suppress vibration significantly for cantilever plate.